Statue of limitations - Collins, Kate, 1951- (Collins, Kate, 1951- Goddess of Greene St. mystery., 2020)
After her divorce, Athena has returned to coastal Michigan to work in her family<U+2019>s garden center and raise her son, while also caring for a mischievous wild raccoon and fending off her family<U+2019>s annoying talent for nagging. Working alone at the garden center one night, Athena is startled by a handsome stranger who claims to be the rightful owner of a valuable statue her grandfather purchased at a recent estate sale. But she has even bigger problems on her plate. The powerful Talbot family from whom her pappoús bought the statue is threatening to raze the shops on Greene Street<U+2019>s “Little Greece” to make way for a condo. The recent death of the family<U+2019>s patriarch already seemed suspicious, but now it<U+2019>s clear that a murderer is in their midst. Athena will have to live up to her warrior goddess namesake to protect her family from a killer and save their community from ruin . . .